Peculiarities of Designing of Suspensions for Stators of High Power Turbogenerators - Tretiak, Oleksii (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2018)
The analysis of existing designs of the stator fastening of Turbogenerators of various design versions is carried out. It is shown that the application of a spring suspension is the integral part of the design of Turbogenerators rated 100 MW and higher. The detailed calculation of the complex stressed state of the stators suspension of Turbogenerators manufactured at SE "PLANT "ELECTROTYAZHMASH" rated 200 MW and 250 MW with hydrogen and hydrogen-water cooling is submitted in the scientific work, taking into account the uneven thermal distribution along the horizontal axis of the aggregate for some number of electrical-sheet steels. The various types of the stator deformation caused by a number of forces are considered. It is proposed to carry out the calculation of mechanical stresses by iterative execution of mechanical and thermal calculations coordinated with electrical stresses. As limiting conditions for taking in to account of forces caused by temperature changes, the limiting conditions of the first kind were considered. At that, in the mechanical calculation, it is necessary to take into account the design peculiarities for each row of springs, taking into consideration the correction for temperature. The key factor is the difference between the calculated vibrations for a stand separately core and its installation in to the casing with suspension, depending up on the modulus of elasticity of the stacked up laminated core for electrical-sheet steels 3413, 3414 GOST21427.1-83, M270-50A. The possibility of changing of steel 38Х2Н2ВА to steel 34CrNiMo6 and steel 40NiCrMo7 is shown, provided that the GOST8479-70 complies with the same strength group.